Predicted antiviral activity of tenofovir versus abacavir in combination with a cytosine analogue and the integrase inhibitor dolutegravir in HIV-1-infected South African patients initiating or failing first-line ART. (31st October 2018) - Derache, Anne; Iwuji, Collins C; Danaviah, Siva; Giandhari, Jennifer; Marcelin, Anne-Geneviève; Calvez, Vincent; de Oliveira, Tulio; Dabis, François; Pillay, Deenan; Gupta, Ravindra K
Abstract: Objectives: The WHO recently recommended the use of a new first-line ART containing dolutegravir. We investigated the efficacy of NRTI backbones (tenofovir or abacavir with a cytosine analogue) in low- and middle-income countries where there is significant prior exposure to antiretrovirals and drug resistance to NRTIs. Methods: Within the treatment-as-prevention study in South Africa, we selected participants with available next-generation sequencing (NGS) data for the HIV-1 pol gene at trial entry; they were either ART initiators ( n = 1193) or already established on ART ( n = 94). NGS of the HIV-1 pol gene was carried out using MiSeq technology; reverse transcriptase drug resistance mutations (DRMs) were detected at 5% (DRM 5% ) and 20% (DRM 20% ) for all 1287 participants. Genotypic susceptibility was assessed using the Stanford HIVDB resistance interpretation algorithm. Results: NRTI DRM 20% and DRM 5% were detected among 5/1193 (0.4%) and 9/1193 (0.8%) of ART initiators, respectively. There was tenofovir exposure in 73/94 (77.7%) of those established on ART, with full susceptibility to abacavir in 57/94 (60.6%) and 56/94 (59.6%) for DRM 20% and DRM 5%, respectively, while 67/94 (71.3%) and 64/94 (68.1%) were fully susceptible to tenofovir, respectively. The differences between tenofovir and abacavir were not statistically significant at the 20% or 5% variant level ( P = 0.16 and 0.29, respectively). NGS detection of variants at the 5% level increased detection of K65R in both naive and treated groups. One of 607 integrase sequences carried a DRM 20% (Q148R). Conclusions: Dolutegravir with a cytosine analogue plus tenofovir or abacavir appears to have similar efficacy in South Africans naive to ART. NGS should be considered in HIV drug resistance surveillance.